Academic Anxiety of Foreign Students in Indonesia and Its Handling: An Educational Psychology Analysis - Baharuddin Baharuddin; Syahril Syahril; Sari Utami; Mutmainna Sudirman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Academic anxiety is a prevalent issue among international students adjusting to unfamiliar educational environments. In Indonesia, foreign students often face emotional stress due to differences in academic systems, communication styles, and cultural norms. This study aims to explore the forms of academic anxiety experienced by foreign students and analyze effective handling strategies from an educational psychology perspective. This research employed a descriptive qualitative approach using fieldwork methods. Data were collected through in-depth interviews and observations involving seven informants, including four international students and three faculty members from a state Islamic university in Indonesia. Secondary data were obtained from institutional documents. Data were analyzed using the Miles and Huberman model through data reduction, display, and conclusion drawing. Validation was conducted through source triangulation and member checking. The findings reveal three major forms of academic anxiety: communication-related anxiety due to language barriers, social anxiety stemming from cultural adjustment, and innovation-related anxiety influenced by limited academic self-confidence. Handling efforts include structured communicative interventions, inclusive socialization programs, and the development of academic self-efficacy. Educational psychology offers a strategic framework to manage academic anxiety through adaptive learning environments and culturally responsive pedagogical practices. Implementing supportive interventions enhances student engagement, self-confidence, and academic achievement. These findings contribute to policy recommendations for improving academic support for foreign students in Indonesia.